2010
DOI: 10.1111/j.1365-2249.2010.04291.x
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor (TLR)-4 mediates anti-β2GPI/β2GPI-induced tissue factor expression in THP-1 cells

Abstract: SummaryOur previous study demonstrated that annexin A2 (ANX2) on cell surface could function as a mediator and stimulate tissue factor (TF) expression of monocytes by anti-b2-glycoprotein I/b2-glycoprotein I complex (anti-b2GPI/ b2GPI). However, ANX2 is not a transmembrane protein and lacks the intracellular signal transduction pathway. Growing evidence suggests that Toll-like receptor 4 (TLR-4) might act as an 'adaptor' for intracellular signal transduction in anti-b2GPI/b2GPI-induced TF expressing cells. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 34 publications
6
43
0
Order By: Relevance
“…This may be of great importance, as the formation of microparticles seems to reflect the severity of DIC (40,41). There is evidence that expression of TF is also dependent on TLR4/MD-2 signal transduction (42). Anti-CD14 may have prevented CD14 transferring LPS to the receptor complex TLR4/MD-2, thereby preventing intracellular signaling (10,11) and subsequent induction of TF.…”
Section: Discussionmentioning
confidence: 99%
“…This may be of great importance, as the formation of microparticles seems to reflect the severity of DIC (40,41). There is evidence that expression of TF is also dependent on TLR4/MD-2 signal transduction (42). Anti-CD14 may have prevented CD14 transferring LPS to the receptor complex TLR4/MD-2, thereby preventing intracellular signaling (10,11) and subsequent induction of TF.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of agonists and interactions can upregulate the expression of TF (Carlsen and Prydz , 1988 ;Cermak et al , 1993 ;Celi et al , 1994 ). More recently, it has been suggested that the toll-like receptors TLR4 and TLR6 contribute to the expression of TF on monocytes and monocytic cells Zhou et al , 2011 ;Owens et al , 2012 ) induced by oxidized low-density lipoproteins and anti-β 2 -glycoprotein I/ β 2 -glycoprotein I. It has been also shown that plateletderived growth factor CC (Gebhard et al , 2010 ) and the platelet factor 4/heparin-antibody complex (Kasthuri et al , 2012 ) can induce monocyte TF expression.…”
Section: Tf Environment and Activitymentioning
confidence: 99%
“…We found that the anti-b2GPI/b2GPI complex could activate the intracellular signalling pathways in monocytes in a manner comparable to that induced by LPS, significantly increase the mRNA and protein levels of TLR4, myeloid differentiation protein 2 (MD-2; LY96) and MyD88, and induce IRAK1 phosphorylation and TRAF6 ubiquitination, ultimately leading to enhanced expression of TF mRNA and activity Zhou et al, 2011). In order to further confirm the effects of the TLR4 axis in anti-b2GPI/b2GPI-induced TF expression in monocytes, we used paclitaxel, which has been reported as a novel approach to block LPS-induced TLR4 expression in monocytes by binding to MD-2 (Resman et al, 2008;Zimmer et al, 2008).…”
Section: Review ª 2013 John Wiley and Sons Ltdmentioning
confidence: 95%
“…Therefore, we subsequently investigated the relationship of TLR4 and ANXA2 in anti-b2GPI/b2GPI-induced TF expression in THP-1 cells in detail and found that, in THP-1 cell lysates, both ANXA2 and TLR4 could bind to b2GPI that had been conjugated to a column packaged with b2GPI-Affi-Gel . Moreover, the anti-b2GPI/b2GPI complex-induced TF mRNA expression, TF activation and expression of TLR4, MyD88, MD-2, IRAKs and TRAFs were remarkably diminished in THP-1 cells infected with lentivirus containing ANXA2-specific RNA interference (RNAi) (LV-RNAi-ANXA2) Zhou et al, 2011). Our results strongly suggested that TLR4 can act as a co-repressor for ANXA2, and TLR4 and its signal transduction pathway contributes to anti-b2GPI/b2GPI-induced TF expression in THP-1 cells (Fig 1).…”
Section: Review ª 2013 John Wiley and Sons Ltdmentioning
confidence: 99%